Prospects of China's biogas: Fundamentals, challenges and considerations. (November 2020) - Giwa, Abdulmoseen Segun; Ali, Nasir; Ahmad, Izhar; Asif, Muhammad; Guo, Rong-Bo; Li, Fu-Li; Lu, Ming
Abstract: This article focuses on the background and current situation of various levels of biogas generation in mainland China. These levels are categorised as rural household, agricultural engineering and industry-based engineering generations. To analyse and forecast China's biogas generation, the Hubbert forecast model was discussed for Chinese provinces. This model was initially applied to the petroleum research industry and can be implemented to biogas prediction. The results validate that total biogas generation may not be achieved in the coming years because of low rural household production and thus contradicts the previous target set by the government. Enhanced bio-natural gas yield is one of main objectives of China's energy sector, which targets 300 × 10 27 m 3 of biogas by 2030. This work evaluates the opportunities and challenges in China's biogas production market. It also provides detailed descriptions of biogas policy and development, national subsidy framework, foreign investments and future perspectives for the establishment of pilot-scale biogas generation. Highlights: The household, agricultural and industry-based biogas plants were discussed. Hubbert model was discussed to analyse and expect the china's biogas forecast. The targeted biomethane need for Chinese state by 2030 was deeply discussed. The opportunity and challenges of China's biogas production market was focused. The detail biogas policy, development, subsidy, foreign investments were focused.